Asymmetric dimethylarginine predicts impaired epicardial coronary vasomotion in patients with angina in the absence of obstructive coronary artery disease. (15th January 2020) - Parikh, Rushi V.; Pargaonkar, Vedant; Ball, Robyn L.; Kobayashi, Yuhei; Kimura, Takumi; Yeung, Alan C.; Cooke, John P.; Tremmel, Jennifer A.
Abstract: Background: Impaired epicardial coronary vasomotion is a potential mechanism of angina and a predictor of adverse cardiovascular outcomes in patients without angiographic evidence of obstructive coronary artery disease (CAD). We sought to evaluate the association of asymmetric dimethylarginine (ADMA)—a marker of nitric oxide-mediated vascular dysfunction—with epicardial coronary vasomotor dysfunction in this select population. Methods: Invasive testing for epicardial vasomotor dysfunction was performed using intracoronary acetylcholine in the left anterior descending coronary artery. Impaired vasomotor response was defined as a luminal constriction of >20% on quantitative coronary angiography. Plasma ADMA levels were measured using high performance liquid chromatography. A robust multivariate linear mixed-effect model approach and Akaike information criterion were used to determine predictors of vasomotor dysfunction. Results: In 191 patients with angina in the absence of obstructive CAD, abnormal epicardial vasomotion was observed in 137 (71.7%) patients. Median ADMA rose as the extent of impairment progressed: none (0.48 [0.44–0.59] μM), any (0.51 [0.46–0.60] μM, p = 0.12), focal (0.54 [0.49, 0.61] μM, p = 0.17), and diffuse (0.55 [0.49, 0.63] μM, p = 0.02). In unadjusted analysis, ADMA was highly predictive of vasomotor dysfunction (χ 2 =15.1, p = 0.002). Notably, ADMA remained a significant predictor even after adjusting for other factors in the best fit model (χ 2 =10.0, p = 0.02). Conclusions: ADMA is an independent predictor of epicardial coronary vasomotor dysfunction in patients with angina in the absence of obstructive CAD. These data support a very early mechanistic role of ADMA in the continuum of atherosclerotic heart disease. Highlights: In patients with nonobstructive CAD, ADMA levels rise as the extent of epicardial coronary vasomotor dysfunction worsens ADMA is an independent predictor of impaired epicardial coronary vasomotion in the nonobstructive CAD population These data suggest a very early mechanistic role of ADMA in the continuum of atherosclerotic heart disease